The Culture of Trauma and the COVID-19 Crisis - Novella, Enric (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2024)
This article reviews the genealogy and main assumptions of trauma culture in view of its extensive application during the recent COVID-19 pandemic. First, it summarises the crystallisation and development of the contemporary doctrine of (psychological) trauma in clinical psychiatry, psychopathology and psychoanalysis. It then presents the (problematic) translational concept of cultural trauma and offers some reflections on the global understanding of human catastrophes (caused by either collective violence or natural disasters) as traumatic events. Finally, it offers some concluding remarks on the contrast between the (relative) relevance of the trauma narrative in accounting for individual suffering and its (limited) performance in reflecting the final course of a health crisis that in its early stages seemed to threaten our way of life and our values.